2014
DOI: 10.1103/physreva.90.062710
|View full text |Cite
|
Sign up to set email alerts
|

Differential cross sections for single ionization of Li in collisions with fast protons andO8+ions

Abstract: We study the process of single ionization of Li in collisions with H + and O 8+ projectile ions at 6MeV and 1.5-MeV/amu impact energies, respectively. Using the frameworks of the independentelectron model and the impact parameter picture, fully (FDCS) and doubly (DDCS) differential cross sections are evaluated in the continuum distorted-wave with eikonal initial-state approxima- respectively. For O 8+ impact inclusion of the heavy particle (NN) interaction in the calculations is crucial and effects of polariza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 32 publications
(131 reference statements)
0
29
0
Order By: Relevance
“…In the present work, in addition to the Coulomb field, a short-range potential is also introduced for a more realistic account of the core electron. Moreover, the polarization of the target core ion by the incident projectile ion is taken into account by a polarization potential [27][28][29]. The indication of single-center interference and the characteristic role of target core polarization are observed at small and large momentum transfer values.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, in addition to the Coulomb field, a short-range potential is also introduced for a more realistic account of the core electron. Moreover, the polarization of the target core ion by the incident projectile ion is taken into account by a polarization potential [27][28][29]. The indication of single-center interference and the characteristic role of target core polarization are observed at small and large momentum transfer values.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of the semiempirical NN potentials were examined in Ref. [9]. It was found that at small momentum transfers, the DDCS is sensitive solely to the asymptotic form of the NN potential at large internuclear distances.…”
Section: Theorymentioning
confidence: 99%
“…1(c)-3(c) of Ref. [12] for the valence-shell ionization DDCSs] by combining the outer-shell ionization amplitude with amplitudes for inner-shell excitations and elastic scattering. While all the processes from (i) to (iv) play an important role in increasing the overall DDCS to match the experimental values at low η, it is the EI2 process that is responsible for the broadening of the DDCS such that it agrees well with the experiment at E e = 2 eV (Fig.…”
Section: B Contributionsmentioning
confidence: 99%
“…With this new approach the first kinematically complete experiment for single ionization of lithium was achieved and experiments were performed for the H + -Li collision system at 6 MeV/amu [6], the O 8+ -Li collision system at 1.5 MeV/amu [6,7], and the Li 2+ -Li collision system at 2.29 MeV/amu [8]. This triggered theoretical efforts for the interpretation of the experimental data [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation